White Men in Quarantine: Disease, Race, Commerce and Mobility in the Pacific, 1872. Issue 2 (3rd April 2017) - Foxhall, Katherine
Abstract : In July 1872, the steamship Hero underwent quarantine at Sydney's North Head after a case of smallpox was diagnosed. This article brings together the histories of quarantine, white subjectivity and Pacific mobility through an analysis of the Loganiana newspaper produced by the passengers of the Hero during their confinement. The Loganiana provides a unique insight into the formation of white identities through discussions of race, commerce, science and inter-colonial politics. The case provides an important perspective on a transformative period in Australia's border history, and also illuminates the tensions accompanying the transition from an older imperial order to political autonomy in the nineteenth-century Pacific.